2020
DOI: 10.3390/cancers12082008
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Induced Hypoxia Enhances miRNA Functions in Breast Cancer

Abstract: In aggressively growing tumors, hypoxia induces HIF-1α expression promoting angiogenesis. Previously, we have shown that overexpression of oncogenic microRNAs (miRNAs, miRs) miR526b/miR655 in poorly metastatic breast cancer cell lines promotes aggressive cancer phenotypes in vitro and in vivo. Additionally, miR526b/miR655 expression is significantly higher in human breast tumors, and high miR526b/miR655 expression is associated with poor prognosis. However, the roles of miR526b/miR655 in hypoxia are unknown. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 60 publications
0
40
0
Order By: Relevance
“…In addition, potential tumor markers for aggressive forms of cancer may help early diagnosis and therapeutic monitoring. As discussed in this review, COX-2 induced miRNAs miR655 and miR526b enhances tumor associated angiogenesis and lymphangiogenesis [35,57] and can serve as biomarkers for breast cancer. In conclusion, the evidence highlighted in this review provides a rationale for the pursuit of EP4 antagonists in combination therapies to treat TNBC and other cancers that display high levels of angiogenesis and lymphangiogenesis..…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In addition, potential tumor markers for aggressive forms of cancer may help early diagnosis and therapeutic monitoring. As discussed in this review, COX-2 induced miRNAs miR655 and miR526b enhances tumor associated angiogenesis and lymphangiogenesis [35,57] and can serve as biomarkers for breast cancer. In conclusion, the evidence highlighted in this review provides a rationale for the pursuit of EP4 antagonists in combination therapies to treat TNBC and other cancers that display high levels of angiogenesis and lymphangiogenesis..…”
Section: Discussionmentioning
confidence: 97%
“…Angiogenesis is an essential physiological process; however, TAA is one of the main hallmarks of cancer progression [55]. In growing tumors, hypoxia is a major mechanism for upregulation of VEGFs, leading to angiogenesis [56,57]. Cancer can lead to abnormal development of blood vessels to promote metastasis.…”
Section: Tumor Associated Angiogenesis (Taa)mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in silico bioinformatics analysis showed that hypoxia-upregulates miR526b/miR655 stabilize HIF proteins targeting the transcription factors NR2C2, SALL4, and ZNF207 that, in turn, regulate PTEN (a negative regulator of HIF-1α) and NFκB1 (positive regulator of COX-2 and EP4) [ 128 ].…”
Section: Feedback Loops Between Hif and The Hypoxia-induced Non-comentioning
confidence: 99%